Martin Lopez-Zubero's Right-arm Pull at 180 m of His 200 m Backstroke Gold Medal Swim at the Barcelona Olympic Games 1992 - Rushall, B. S. (1999)
Video pictures (9 frames) and the appropriate technical/ biomechanical explanations for Martin Lopez-Zubero's Right-arm Pull at 180 m of His 200 m Backstroke Gold Medal Swim at the Barcelona Olympic Games 1992. Martin Lopez-Zubero demonstrates a propulsive coordination between both arms which allows very little inertial lag between each pull. As the inward scull of the right arm is completed the left arm is already into propulsion (frame #9). This continual application of force is desirable and efficient. The directness of the swimmer's pull is notable. Instead of sweeping outward in the early stage and inward in the latter, the right arm bends early and considerably to generate propulsive forces backward. It remains wide as adduction of the upper arm is completed. This has to occur if an effective inward scull is to be produced.